2021
DOI: 10.11606/1807-0205/2021.61.50
|View full text |Cite
|
Sign up to set email alerts
|

Variation in dung beetle (Coleoptera: Scarabaeidae: Scarabaeinae) assemblages in a tropical forest remnant from a Mexican National Park

Abstract: The Cañón del Sumidero National Park (PNCS) is a priority area for conservation, but there are few studies on its fauna, which evidences the need for further basic studies to produce adequate knowledge on its biodiversity. This study aimed to determine dung beetle assemblages temporal distribution, trophic preference, and daily activity patterns. We conducted samplings using baited pitfall traps in a PNCS tropical sub deciduous forest remnant, during the dry and rainy seasons between 2014 and 2015. We captured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0
4

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 33 publications
0
4
0
4
Order By: Relevance
“…and Sánchez-Hernández et al. (2021; 20 spp. ), and most of the species (∼80%) are also commonly found in the tropical deciduous forests of the Central Depression region of Chiapas (Sánchez-Hernández et al.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…and Sánchez-Hernández et al. (2021; 20 spp. ), and most of the species (∼80%) are also commonly found in the tropical deciduous forests of the Central Depression region of Chiapas (Sánchez-Hernández et al.…”
Section: Discussionmentioning
confidence: 89%
“…At a regional scale, the found richness accounts for about 70% of the species reported by Arellano et al (2013) and Sánchez-Hernández et al (2022a), whereas the species richness obtained was similar to that reported by Rodríguez-López et al (2019;22 spp. ) and Sánchez-Hernández et al (2021;20 spp. ), and most of the species (∼80%) are also commonly found in the tropical deciduous forests of the Central Depression region of Chiapas (Sánchez-Hernández et al 2020).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…En los Estados Unidos se le registró consumiendo insectos muertos y hongos (Young 2006); en Argentina se le encontró en trampas cebadas con excremento humano y carroña (Gómez 2005) y en Brasil, se ha recolectado en estiércol de aves de corral (Gianizella y Prado 1999;Lopes et al 2007), así como en trampas cebadas con carroña, estiércol de ganado bovino, de cerdo doméstico y heces humanas (Correa et al 2013). Sin embargo, estudios realizados en Chiapas en los que se han utilizado atrayentes similares a los mencionados para el muestreo de escarabajos, no reportan la captura de esta u otra especie de Trogidae (e.g., Arellano et al 2013;Sánchez-Hernández et al 2018, 2019, 2022, incluido el trabajo de Sánchez-Hernández et al (2021), quienes utilizan el estiércol de Panthera onca como atrayente.…”
unclassified